Measures of food insecurity at the household level - Indranil Dutta; Craig Gundersen; Prasanta K. Pattanaik (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
Food insecurity and hunger have traditionally been measured by aggregate food supplies or by variables correlated with food insecurity. Because these measures often poorly reflect individuals' true deprivation, economists have turned to surveys with direct questions about food insecurity. Using these surveys, households have then been classified into broad categories, a classification system which ignores the richness of the multiple questions. In this paper, we propose food insecurity measures, along the lines of the well established poverty measures, which incorporates this richness and allow us to reflect the depth and severity, in addition to the incidence, of food insecurity. Using these indices, we calculate the extent of food insecurity and hunger in the United States. Along with giving a richer picture of food insecurity in the US, these food insecurity measures demonstrates that the ordering of various demographic categories differs depends on the choice of measure. – deprivation ; food insecurity ; hunger ; poverty measures
Keywords: D63; I31; I38; 330; Nahrungsmittelversorgung; Unterernährung; Armut; Messung; USA